PERAN ETIKA PROFESI HUKUM DALAM MENINGKATKAN PROFESIONALISME HUKUM DI INDONESIA - Mustaqim, Dede Al; Samsiah, Yunistika; Nurfatiha, Siti Rifela (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2023)
This research aims to explore understanding of the legal profession, related fields, professionalism issues, moral value criteria, attitudes that must be held, and the role of legal professional ethics in increasing legal professionalism in Indonesia. The method used in this research is a qualitative method with a literature study approach. The research results show that the legal profession is a discipline that plays an important role in providing legal services to the community. There are diverse fields within the legal profession, and professionalism issues such as corruption, ethical violations, and limited public access to the legal system are major challenges. High moral value criteria, such as integrity and honesty, as well as ethical attitudes, such as independence and social responsibility, are considered crucial for legal professionals. Legal professional ethics plays a major role in ensuring that legal practitioners carry out their duties to high ethical standards. The conclusion of this research is the importance of understanding and applying moral and ethical values ​​in the practice of the legal profession as a step towards improving legal professionalism in Indonesia.